Parenting From the Outside‐in: Reflections on Parent Training During a Potential Paradigm Shift. (2nd May 2013) - Coyne, Joe
<x xml:space="preserve">Abstract</x> This article proposes that a paradigm shift that has implications for practitioners of parenting interventions is emerging. This shift represents a challenge to the dominant model of parent training. The Triple P Parenting Program is discussed as an example of parent training programme to highlight the relevant issues for practitioners, including common practitioner objections encountered in dissemination as identified, in part, by Mazzucchelli and Sanders. It is argued that apart from these objections, there are more essential concerns in relation to the adoption of parent training programmes by practitioners. Rather, the article argues that parent training is "mind‐blind" and that approaches emerging from the field of interpersonal neurobiology represent developmentally sophisticated alternatives for intervention. The Circle of Security programme is discussed as one example of this emerging paradigm shift that integrates attachment, social neuroscience, and psychodynamic theory. Contrasts are highlighted between the models, and considerations for future issues in parent intervention conclude the article.